Supervision of School and Community Relations Management at Mts Ummul Quro Al-Islami - Nesia Andriana; Wido Supraha; Buldan Nurjaman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Supervision of School-Community Relations is important in supporting the education process. Quality education must have good and measurable supervision management. Supervision as a controlling process in carrying out educational activities in schools must guarantee the quality of the output produced by these educational institutions. The role of the community in supervising educational institutions is very important and even necessary in determining the future direction of education policy. Realizing quality education, able to answer future challenges and various problems that exist in society. This article explains how the supervision of school relationship management with the community at MTs Ummul Quro Al-Islami Leuwiliang, Bogor.